PELANGGARAN PRINSIP KERJA SAMA PERCAKAPAN DALAM ACARA MATA NAJWA DI METRO TV - Afif Setiawan; Rokhmat Basuki; Ngudining Rahayu (Jurnal Korpus, 2017)
The purpose of this study is to describe the form of violations of the principle of cooperation of conversation in the event of Mata Najwa on Metro TV. The method used in this research is descriptive qualitative method. The data source in this research is Najwa Shihab speech and its speaker in Mata Najwa on Metro TV. The data in this study were three episodes of Mata Najwa  events in June, August, and December namely: the episode of "Luhut Controversy" which aired on June 1, 2016, "Miscellaneous Lawyers" which aired on August 31, 2016, and the episode "Moves Demi Hak "which aired on December 21, 2016. Data collection techniques use the documentation method. Data analysis technique in this research is done through the steps, that is transcribing data, identifying data (encoding), classifying data in table form, interpreting data, and concluding research result. The results of the study found 130 violations of the principle of conversational cooperation with details, 56 (43%) maxim quantity violations, 10 (7.8%) maxim quality violations, 34 (26.5%) maxim relevance breaches, and 30 (22.6% ) Violation of the way maxim. In this study, it was classified into two forms of violation of the principle of conversational cooperation, namely the single maxim and multiple maxim violations, with details of 75 utterances with single maximal offenses and 26 speeches with double maxim breaches. Factors behind the breach of the principle of conversational cooperation in Mata  Najwa on Metro TV, namely: maximizing wisdom, maxima agreement, maxim of simplicity, maxim of generosity, maxim of appreciation, maxim of conclusion, the concept of negative face and face rescue.